Effect of Exposure and Storage Conditions on the Levels of Iodine in Selected Iodated and Non-Iodated Salts in Ghana - Laar, Cynthia; Pelig-Ba, K.B. (Pakistan Journal of Nutrition, 2012)
Iodated salt is the best means of providing iodine to deficient populations, and it has been used successfully and safely over the past 70 years around the world. Since iodine readily sublimes at high temperatures, iodate is typically used due to its better resistance to oxidation. The actual availability of iodine from iodated salt at the consumer level can vary widely due to a number of factors, including the variability in the amount of iodine added during production, storage and meal preparation. The stability of iodine in typical salts available in the country’s market were determined under different storage conditions such as in the fridge, cupboard, exposure to direct sunlight for several days to mimic how salts are usually stored. Iodine levels dropped slowly in most iodated salt ranging from less than 10% to 30% of the added iodine but dropped rapidly from less than 10% to 100% in the raw non iodated salts. The reason was that the latter did not have stabilizers. While there is a wide band of iodine intake levels that are safe to consume, it is important that adequate amounts are delivered to the consumer. Therefore it is critical to have an accurate estimate of the losses in iodine prior to consumption, so that the producers may compensate for the losses.